The state of Lithuanian mathematical terminology in the post war period - Pekarskas, Vidmantas; Pekarskienė, Albina (Lietuvos matematikos rinkinys, 2002)
The status of Lithuanian mathematical terminology in the period after the Second World War was investigated. The Lithuanian terminology of elementary and higher mathematics was discussed there.